PEMAHAMAN HADIS MELALUI KONTEN ANIMASI 'HAFIZ HAFIZAH': MEMBANGUN PENDIDIKAN ANAK YANG ISLAMI DI ERA DIGITAL - Mas Ayu Ainun Nisa’; Mohammad Kurjum (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
In the midst of rapid technological development, animation media has become one of the most effective educational tools for introducing Islamic values to children, including the study of hadith. Over time, hadiths have been presented through engaging media such as animated content. Given the importance of hadith as the second source of Islamic law after the Qur'an, accuracy and appropriateness in conveying hadiths through any medium, including animation, becomes a crucial issue. This study aims to analyze the conformity of the understanding of hadiths presented in the